Finding best coefficient and fusion of coefficients for similarity searching using neural network algorithms [compact disc] - 205057 Norhayati Daut (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005